A new characterization of projective special linear groups L₃(q) - Ebrahimzadeh, B. (Algebra and Discrete Mathematics, 2021)
In this paper, we prove that projective special linear groups L₃(q), where 0 < q = 5k ± 2 (k ∊ Z) and q² + q + 1 is a prime number can be uniquely determined by their order and the number of elements with same order.